Comparison of Mean Dimensional Stability of Self Disinfecting Alginate Impressions with Alginate Impression Disinfected Through Immersion Method - Uzma Khalil, Shafqat Hussain, Sadaf Khan, Mehreen Nawaz, Amna Mansur, Hamad Ishtiaq Mian, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The aim of this study was to compare the mean dimensional stability of self-disinfecting alginate impressions with alginate impression disinfected through immersion method. Materials and Methods: A total 394 edentulous patients were randomly allocated in two groups: Group A (self-disinfecting alginate (mixed with chlorhexidine), Group B (soaked in disinfectant (immersed in chlorhexadine). Impressions from patients in group A were subjected to self disinfection via chlorhexidine mixed with alginate powder, Group B: Alginate impressions obtained from patients were subjected to disinfection with chlorhexidine via immersion method. Post disinfection anteroposterior and medio-lateral dimensions were recorded using electronic digital caliper. The data was analyzed using SPSS version 10.0. Student-t test was applied for anteroposterior and mediolateral dimensions. The confidence interval was 95% and p<0.05 was kept as statistically significant. Results: The mean age in group A was 64± 3.75 years, while the mean age in group B was 62± 2.17 years. In group A, 89(45%) patients were male and 108(55%) patients were female. While in group B, 93(47%) patients were male and 104(53%) patients were female. Mean anteroposterior dimension (AB) in group A was 35.82± 0.06mm. Where mean anteroposterior dimension (AB) in group B was 35.91±0.07mm. Mean Medio lateral dimension (BC) in group A was 35.66± 0.05mm. While Mean Medio lateral dimension (BC) in group B was 35.73±0.06mm. Conclusion: This study concludes that mean dimensional change values in self disinfecting alginate was similar to that of an alginate impression immersed in 0.2 percent chlorhexidine solution. Keywords: Alginate impression, self disinfecting alginate, alginate impression, immersion,disinfection.